The Role of Libraries in the Missionary Regions of Orinoquia - del Rey Fajardo S.J., José (Journal of Jesuit studies, 2015)
Beginning in 1661, the Jesuits conducted missionary activity in the Orinoquia [the Orinoco delta]. Among the more significant challenges was the introduction of literacy to a people whose concepts of history and society were quite foreign to Spanish and Italian priests. Creating Christians would therefore entail creating a literate culture: the Jesuits began by learning local traditions and committing these to paper, and only then teaching the children of the region to read and write. While none of these teaching books survive, the missionary schools and houses kept libraries which included volumes on regional crafts and history, along with items the Jesuits considered useful or necessary: music, instruments, and books authored by members of the Society. The inhabitants of the Orinoco River watershed thus had access to European books as well as those in indigenous languages, both of which simultaneously supported and shaped life within the missions and reductions.